Effects Of Ginkgo biloba Versus Celecoxib On The Levels Of Oxidative Stress And Matrix Metalloproteinase-1 In Patients With Knee Osteoarthritis - Khalid Ismael, Inaas; Hahim Othman, Shamil (Tikrit Journal of Pharmaceutical Sciences, 2023)
To investigate the effects of Ginkgo biloba (GB) and Celecoxib on the parameters of oxidative stress (OS) and matrix metalloproteinase-1(MMP-1) concentration and the markers of inflammation in patients with knee osteoarthritis (KOA). To achieve the aim of this study, a randomized control trial(RCT) was adopted. A total of 80 patients with KOA were recruited and investigated for parameters of OS which included: malondialdehyde (MDA), total antioxidant status (TAS) and serum MMP-1 concentration, in addition to measuring the markers of inflammation such as C-reactive protein (CRP) and erythrocyte sedimentation rate (ESR). The patients were divided into 2 groups namely, the GB plus celecoxib group which consisted of 40 patients(with mean ± SD= 51.10 ± 9.78) and the Celecoxib group which consisted of 40 patients(with mean ± SD=51.47±6.26). The patient groups were followed- up for 8 weeks during which the parameters under study were measured before starting therapies and at the end of the follow-up period using commercially available kits. The patient groups were compared with a control group consisted of 40 apparently healthy subjects. By comparing the concentrations of MDA,TAS and MMP-1 in patients with KOA before and after therapy , there was a highly significant decrease (p<0.001) in serum MDA concentration and a significant decrease (p=0.02) in MMP-1 levels with a highly significant increase (p<0.001) in TAS values after two months use of GB plus celecoxib and celecoxib alone, but with results in favor of the former group. GB plus celecoxib seemed to produce a highly significant decrease (p<0.001) in CRP and ESR compared to celecoxib after two months of therapy. The use of GB plus celecoxib and Celecoxib alone for 8 weeks in KOA patients have beneficial effects on the parameters of OS, MMP-1 and inflammatory markers.